Discussion of "Rocking vibration of a rigid disk embedded in any depth of a coupled seawater-visco-poro-elastic seabed half-space" by R. He [Soil Dyn. Earthq. Eng. 85(2016), 130–133]. Issue 104 (January 2018) - Ahmadi, S.F.; Samea, P.; Eskandari, M.
Abstract : Highlights: Some robust comments have been made on the "Rocking vibration of a rigid disk embedded in any depth of a coupled seawater-visco-poro-elastic seabed half-space" by R. He [Soil Dyn. Earthq. Eng. 85(2016), 130–133]. The proper boundary conditions have been addressed in this discussion. It is inferred that the presented results are not realistic.